Cell-Free DNA Derived From Neutrophils Triggers Type 1 Interferon Signature in Neuromyelitis Optica Spectrum Disorder. Issue 3 (24th May 2022) - Murata, Hisashi; Kinoshita, Makoto; Yasumizu, Yoshiaki; Motooka, Daisuke; Beppu, Shohei; Shiraishi, Naoyuki; Sugiyama, Yasuko; Kihara, Keigo; Tada, Satoru; Koda, Toru; Konaka, Hachiro; Takamatsu, Hyota; et al.
Abstract : Background and Objectives: Recently accumulating evidence suggests the pivotal role of type 1 interferon (IFN-1) signature in the pathogenesis of neuromyelitis optica spectrum disorder (NMOSD). However, the mechanism of the initial trigger that augments IFN-1 pathway in the peripheral immune system of NMOSD has yet to be elucidated. Methods: Clinical samples were obtained from 32 patients with aquaporin-4 antibody–positive NMOSD and 23 healthy subjects. IFN-1 induction in peripheral blood mononuclear cells (PBMCs) by serum-derived cell-free DNA (cfDNA) was assessed in combination with blockades of DNA sensors in vitro. CfDNA fraction was analyzed for DNA methylation profiles by bisulfite sequencing, elucidating the cellular origin of cfDNA. The induction of neutrophil extracellular trap related cell death (NETosis) was further analyzed in NMOSD and control groups, and the efficacy of pharmacologic intervention of NETosis was assessed. Results: Enhanced IFN-1 induction by cfDNA derived from NMOSD was observed in PBMCs with cofactor of LL37 antimicrobial peptide. DNase treatment, cGAS inhibitor, and Toll-like receptor 9 antagonist efficiently inhibited IFN-1 production. DNA methylation pattern of cfDNA in patients with NMOSD demonstrated that the predominant cellular source of cfDNA was neutrophils. Whole blood transcriptome analysis also revealed neutrophil activation in NMOSD. In addition, enhanced NETosis induction was observed with NMOSD-derived sera, and efficient pharmacologic inhibition of NETosis with dipyridamole was observed. Discussion: Our study highlights the previously unrevealed role of cfDNA predominantly released by neutrophil in the induction of IFN-1 signature in NMOSD and further indicate a novel pharmacologic target in NMOSD.